Identifying the Role of YAP in the Development of Rumen Epithelium Using 3D Organoid - Zebang Xu; Xinxin Xu; Yuling Mi; Yuanyuan Zhang; Qihua Hong; Bin Yang; Jiakun Wang (Stem Cells International)
Ruminants are of significant economic importance, and their unique digestive system features the rumen as a vital organ. The rumen is lined by stratified squamous epithelium, plays a crucial role in absorbing volatile fatty acids (VFAs) generated through microbial fermentation, thereby meeting the daily energy requirements of these animals. The maintenance of the rumen epithelium is a matter of concern. Here, we present compelling evidence that the hippo pathway effector yes-associated protein 1 (YAP) serves as a key regulator in maintaining rumen epithelial cells (RECs). Our findings indicate that rumen epithelial basal cells spontaneously undergo expansion and differentiation, ultimately forming organoids, and that the hippo signaling pathway is involved in regulating this process. Specifically, we demonstrate that YAP is indispensable for the initial specification and long-term maintenance of organoids. Activation of YAP promotes the growth and formation of these organoids, whereas inhibiting YAP hinders this developmental process. YAP activation exerts its effects by enhancing basal cells proliferation while simultaneously inhibiting differentiation. Conversely, YAP inhibition reduces the proliferation of basal cells. Notably, YAP activation promotes dedifferentiation of differentiated organoids. Moreover, YAP activation fosters intercellular tight junctions and strengthens cell-extracellular matrix interactions. In contrast, YAP inhibition reverses these features and leads to the disintegration of the organoids. Collectively, our data reveal the regulatory role of YAP in the rumen epithelium, which will help deepen the understanding of rumen development.